Plants Used for Traditional Medicine during Pregnancy, Childbirth, and Postpartum Care by Chuktia Bhunjia Tribe of Nuapada District, Odisha - Jaiminee Jhankar; Damayanti Giri; Jay Prasad Jena; Dr. Rashmi Mohaptara (The Bioscan, 2025)
The use of medicinal plant species against a wide range of diseases has a long history in human civilization, which dates back to the time when people were seeking remedies in their surroundings to help them recover from illness. Activities and diet during the postpartum period are culturally dictated in many tribal cultures and a period of confinement is observed. Plants play an important role in diet and traditional medicine recovery postpartum. Little is known of the Chuktia Bhunjia, a particularly vulnerable tribal group (PVTG) who lives in Sunabeda village of Nuapada District. The primary objective is to identify the use of plants during pregnancy, parturition, postpartum recovery, and infant healthcare.